An investigation into clustering routing protocols for wireless sensor networks - Salami, Abdulazeez F.; Anwar, Farhat; Priantoro, Akhmad Unggul (International Frequency Sensor Association (IFSA)., 2009)
Recent advances in wireless sensor technology have led to the evolvement of new protocols specially designed for wireless sensor networks where energy conservation is of utmost importance. Most of research effort and focus, however, has been concentrated on routing protocols since they might differ depending on the application and network architecture used in their design. Cluster-based routing protocols for large-scale wireless sensor networks are more advantageous compared to flat-based routing protocols. Clustering minimizes the number of messages that are propagated throughout the network whenever an event is sensed. In this paper, an investigation into clustering routing protocols for wireless sensor networks is presented together with a highlight of their key features for comparison.